International Scientific Siberian Transport Forum TransSiberia - 2021 Volume 1 - Manakov, Aleksey; Edigarian, Arkadii; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The book presents latest developments in the field of high-speed railway, Hyperloop transportation technologies and Maglev system. In recent years, railway transport has received a powerful impetus in its development. With the advent of the 4th Industrial revolution, the transport sector is moving towards full digitalization. TransSiberia is a platform where both the rail industry and the communications industry can meet and converge. The book contains papers prepared by experts from both sectors. This is primarily research in the field of the ICT technologies, which will be used for the future railway system. The results of studies on the design of intelligent autonomous transport systems and the operation of high-speed railways in the harsh weather conditions of Siberia are presented in detail. The book presents the state of the art in smart grid technology for railway power systems. This will contribute to decarbonization of the railway. The presented technical innovations in railway science and engineering will help scientists and engineers create a new generation of trains running on alternative fuels and capable of functioning without interruptions in any climatic conditions.
Keywords: Transportation engineering; Traffic engineering; Electric power production; Transportation Technology and Traffic Engineering; Electrical Power Engineering; Transportation -- Congresses